Class III Pistil-Specific Extensin-Like Proteins from Tobacco Have Characteristics of Arabinogalactan Proteins - Bosch, Maurice (American Society of Plant Physiologists, 2001)
Class III pistil-specific extensin-like proteins (PELPIII) are specifically localized in the intercellular matrix of tobacco (Nicotiana tabacum) styles. After pollination the majority of PELPIII are translocated into the callosic layer and the callose plugs of the pollen tubes, which could suggest a function of PELPIII in pollen tube growth. PELPIII may represent one of the chemical and/or physical factors from the female sporophytic tissue that contributes to the difference between in vivo and in vitro pollen tube growth. PELPIII glycoproteins were purified and biochemically characterized. Because of their high proline (Pro) and hydroxy-Pro (Hyp) content, PELPIII proteins belong to the class of Pro/Hyp-rich glycoproteins. The carbohydrate moiety of PELPIII is attached through O-glycosidic linkages and comprises more than one-half the total glycoprotein. Deglycosylation of PELPIII revealed two backbones, both reacting with PELPIII-specific antibodies. N-terminal amino acid sequencing of these backbones showed that PELPIII is encoded by the MG14 and MG15 genes. Two heterogeneous N-terminal sequences of MG14 and MG15, both starting downstream of the predicted signal peptide cleavage site, seem to be present, which indicates a novel N-terminal processing. Monosaccharide analysis showed that the carbohydrate moiety of PELPIII almost completely consists of arabinose and galactose in an equal molar ratio. Carbohydrate linkage analysis showed terminal and 2-linked arabinofuranosyl residues, as well as terminal and 6-, 3-, and 3,6-linked galactopyranosyl residues to be present, indicating the presence of both extensin-like and Type II arabinogalactan oligosaccharide units. The ability of β-glucosyl Yariv reagent to bind with PELPIII confirmed the arabinogalactan protein-like characteristics of these proteins.